Advances and opportunities in the model predictive control of microgrids: Part II–Secondary and tertiary layers. (January 2022) - Babayomi, Oluleke; Zhang, Zhenbin; Dragicevic, Tomislav; Heydari, Rasool; Li, Yu; Garcia, Cristian; Rodriguez, Jose; Kennel, Ralph
Highlights: MPC in secondary centralized, decentralized and distributed architectures. MPC of energy management of autonomous and interconnected microgrids. MPC of power flow for interconnected microgrids. Stochastic predictive energy management of microgrids. Predictive multi-agent control of microgrids. Abstract: Model predictive control (MPC) facilitates the multi-variable control of power electronic systems while accommodating physical constraints without the necessity for a cascaded structure. These features result in fast control dynamic response and good performance when system involving non-linearities . In this second part of this paper, we present a review of the recent advances in the application of MPC to the secondary and tertiary control of microgrids (MGs). We also present comprehensive surveys of MPC techniques to the energy management and power flow control of autonomous and networked MGs. The application opportunities for MPC to both distributed secondary control and networked microgrids are also discussed.